2008
DOI: 10.1159/000111635
|View full text |Cite
|
Sign up to set email alerts
|

Parental Opinions about the Expansion of the Neonatal Screening Programme

Abstract: Background: Advances in genomics will open up opportunities in the fields of genetic testing, early diagnosis and disease treatment. While neonatal screening is the field of application par excellencefor these developments, the debate on its potential benefits and drawbacks is mainly theoretically driven and based on the opinions of professionals. Methods: We conducted a qualitative study of the perceptions, preferences and needs of parents (and parents to be) with respect to expansion of the neonatal screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…[13][14][15][16]55 whereas studies that have explicitly considered harms (although not overdiagnosis) showed some acknowledgment by parents or members of the public but do not illuminate how harms and benefits should be traded off. 1,9,54,56 These findings also add to a broader literature on attitudes toward population screening by exploring several complex harms. [57][58][59][60][61][62][63][64][65][66] Specifically, that 100% of our respondents showed a statistically significant preference to avoid harms (FPs, overdiagnosis) is important, because misunderstanding of risk-based harms is common, 67 and recent work exploring attitudes toward overdiagnosis in the context of breast cancer screening has shown considerable confusion as well as limited valuation.…”
Section: Figurementioning
confidence: 56%
See 1 more Smart Citation
“…[13][14][15][16]55 whereas studies that have explicitly considered harms (although not overdiagnosis) showed some acknowledgment by parents or members of the public but do not illuminate how harms and benefits should be traded off. 1,9,54,56 These findings also add to a broader literature on attitudes toward population screening by exploring several complex harms. [57][58][59][60][61][62][63][64][65][66] Specifically, that 100% of our respondents showed a statistically significant preference to avoid harms (FPs, overdiagnosis) is important, because misunderstanding of risk-based harms is common, 67 and recent work exploring attitudes toward overdiagnosis in the context of breast cancer screening has shown considerable confusion as well as limited valuation.…”
Section: Figurementioning
confidence: 56%
“…[68][69][70][71] Furthermore, the identification of both positive and negative preferences for early diagnosis reinforces qualitative research that suggests the complexity of beliefs about early knowledge of disease in an infant, including concern about the risk of unwanted knowledge and negative consequences for the parent-child bond. 1,9,54 The identification of a negative preference is an important corrective to the literature that identifies early knowledge as valuable in itself, by permitting family adjustment and planning, and averting difficult "diagnostic odysseys." 18,19,22 Finally, our finding that reproductive risk information was the least important attribute should factor into deliberations about the pursuit of reproductive benefit through NBS.…”
Section: Figurementioning
confidence: 99%
“…[31][32][33] Studies of families of children with other conditions vary in the extent to which the availability of a known condition-specific treatment affects parent opinions. [34][35][36] But consistent with most of these studies, many parents of children with FXS felt that earlier identification would enable access to early intervention and therapy services, even though those services are not FXS specific and their efficacy with FXS has not been demonstrated. This finding suggests that parents generally have a broad view of what constitutes treatment and treatability.…”
Section: Discussionmentioning
confidence: 93%
“…10,22,26,27,29,43 The critics of newborn screening in the absence of immediate treatment cite the following reasons:…”
Section: Parental Attitudes Toward Newborn Screeningmentioning
confidence: 99%
“…26 Although some parents expressed concern that parents would be overprotective of asymptomatic diagnosed children, 26,29 others felt it was unlikely. 43 Support for newborn screening did not vary by most parental characteristics.…”
Section: Parental Attitudes Toward Newborn Screeningmentioning
confidence: 99%